Pengaruh Terapi Pijat Kaki Terhadap Hasil Mean Arterial Pressure (MAP) Penderita Hipertensi Pada Lansia di Wilayah Kerja Puskesmas Kalijati - Muhamad Refangga; Dwi Diana Putri; Yenny Makahghi (Jurnal Ventilator, 2024)
Introduction: Hypertension is a chronic condition in which blood vessel walls experience increased blood pressure, requiring a faster heart rate to pump blood throughout the body. The presence of hypertension influences changes in the results of mean arterial pressure, if the mean arterial pressure is more than 100 mmHg it can cause cerebral circulation disorders resulting in cerebral vascular resistance in hypertensive patients. One non-pharmacological effort to overcome and reduce MAP can be done by providing foot massage therapy. Method: This type of research is quantitative research with a pre-experimental one group pre-post test design approach. The instruments used by researchers were a digital spygmomanometer and observation sheet. Results: Descriptive statistical results showed that the average MAP value before giving a foot massage was 112.49 mmHg and the average MAP after giving a foot massage was 108.43 mmHg. Conclusion: The results of the Wilcoxon sign rank test, a non-parametric statistical test, obtained a p value of 0.000 (? = 0.05). So that p < a, it can be concluded that H0 is rejected and H1 is approved, this shows that foot massage therapy can influence the results of mean arterial pressure in elderly hypertensive patients in the Kalijati Health Center working area. This research is expected to provide initial information by carrying out foot massage therapy 6 times in 6 consecutive days as an effort to control hypertension and reduce mean arterial pressure (MAP) results.